2002
DOI: 10.1197/aemj.9.8.800
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Guidance versus the Landmark Technique for the Placement of Central Venous Catheters in the Emergency Department

Abstract: Objective: To compare ultrasound (US)-guided vs. landmark-guided techniques for central venous access (CVA) in the emergency department. Methods: This was a prospective study of consecutive patients enrolled at a university teaching hospital with an annual census of approximately 100,000. On even days patients had CVA with ultrasonic assistance; patients presenting on odd days had CVA via traditional landmark techniques. Ultrasound users were emergency medicine faculty or residents who completed a one-hour t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
0
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(99 citation statements)
references
References 19 publications
9
84
0
6
Order By: Relevance
“…Studies are limited to the description of the procedure and the approximate time involved of the course as well as the "how I do it" approach. 11,17,24,25 There is also a higher awareness and promotion of simulation for training purposes to improve patient safety. 26 This small-scale study demonstrates the effectiveness and efficiency of this multimethod training program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies are limited to the description of the procedure and the approximate time involved of the course as well as the "how I do it" approach. 11,17,24,25 There is also a higher awareness and promotion of simulation for training purposes to improve patient safety. 26 This small-scale study demonstrates the effectiveness and efficiency of this multimethod training program.…”
Section: Discussionmentioning
confidence: 99%
“…5 Ultrasound-guided (USG) insertion of CVCs is reported to be the preferred method for difficult cannulations, such as in those patients with obscure surface landmarks or hypotension. [9][10][11][12][13] Several meta-analyses and randomized controlled trials have demonstrated that USG insertion of CVCs is safely performed by emergency physicians with greater success and fewer immediate complications than the traditional landmarking method. 4,9,11,12,[14][15][16][17] National recommendations have been made for USG insertion of CVCs by both the National Quality Forum in the United States and the National Institute of Clinical Excellence in the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%
“…The literature supports the ability of general emergency physicians to use point-of-care US to improve the care of adult patients by accurately diagnosing time-sensitive and common ED conditions, decreasing patient lengths of stay, 15,[39][40][41] and reducing complications. 15,[42][43][44][45] Furthermore, emergency physicians are able to achieve competency in performing point-of-care US for various indications after completing adequate training. 20,26,[46][47][48] Point-of-care US in pediatric patients by PEM providers has recently been adopted into practice, and the literature is still evolving.…”
Section: Diagnostic and Procedural Indicationsmentioning
confidence: 99%
“…There was also no mention of studies such as those published by Plummer et al 7 and Rozycki et al 8,9 that showed the utility and improved outcome of patients with penetrating chest injuries who were evaluated by sonography. Contributions from other emergency physicians in areas such as aorta, 10-13 gallbladder, [14][15][16] renal, 17 pelvic, [18][19][20][21][22] and vascular [23][24][25][26][27][28][29] sonography were also left out. Finally, indications for ultrasound that are specific to emergency medicine such as the sonographic evaluation of the patient presentation of cardiac arrest, hypotension, and undifferentiated shock were not discussed.…”
Section: History Of Emergency Ultrasoundmentioning
confidence: 99%